(untitled) (Annals of Medical Research, 2021)
Aim: Chronic hyperglycemia can cause cognitive impairments such as learning and memory impairment. In our study, we aimed to investigate the levels of glial fibrillary acidic protein (GFAP), neural cell adhesion molecules (NCAM), lipid peroxidation (LPO), and glutathione (GSH) molecules and the protective effect of melatonin in the brain tissue of baby rats with diabetic mothers. Materials and Methods: Wistar-Albino rats used in the experiments were obtained from Firat University Experimental Research Center. Morris Water Maze Test is a learning and memory test commonly used in rats and mice. In the statistical analysis of the data; one-way analysis of variance (One-way ANOVA) was used to evaluate the significance of NCAM, GFAP, LPO, GSH levels between three groups, and repeated measures analysis of variance (Repeated measures one-way ANOVA) was used to evaluate the Morris Water Maze learning test. Results: Learning was worse in rats whose mothers were diabetic compared to diabetes + melatonin and control groups. With the administration of melatonin to diabetic mothers during their pregnancy, an improvement was observed in the learning ability of baby rats. NCAM 180, GFAP, GSH levels were significantly lower (p <0.05, p <0.001, p <0.05), and LPO level was higher (p <0.001) in baby rats with diabetic mothers compared to the control group. NCAM 180 and GFAP levels were significantly higher in the group that was administered melatonin during pregnancy (p <0.05, p <0.01), and LPO levels were lower (p <0.01). With the administration of melatonin during pregnancy, GSH levels were higher than the diabetes group, even though the difference was not statistically significant. Conclusion: Learning and memory functions are impaired in the offspring of diabetic mothers. The decrease in NCAM isoforms can inhibit brain development and the formation of synaptic plasticity. Decreased GFAP density may pose a problem in completing brain maturation in offspring of diabetic mothers. It has been observed that the administration of melatonin to diabetic mothers during their pregnancy is protective against the harmful effects of oxidative stress in their offspring due to its antioxidant effect.